2015
DOI: 10.1310/sci2103-250
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Bladder and Urodynamic Outcomes in Patients with Spinal Cord Myelopathy

Abstract: Future studies should ascertain whether our screening protocol is appropriate, and a longer-term follow-up should examine the relationship between UD recommendations and prevention of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The electronic search of MEDLINE and Embase identified 6 potentially relevant publications. [13][14][15][16][17][18] After reviewing these articles in detail, we found that none met the inclusion criteria (Figure 1). As a result, the publications included in this review were all identified from our libraries.…”
Section: Literature Searchmentioning
confidence: 99%
“…The electronic search of MEDLINE and Embase identified 6 potentially relevant publications. [13][14][15][16][17][18] After reviewing these articles in detail, we found that none met the inclusion criteria (Figure 1). As a result, the publications included in this review were all identified from our libraries.…”
Section: Literature Searchmentioning
confidence: 99%
“…A previous study in a cohort of patients with nontraumatic spinal cord myelopathy showed that 46% voided guided by sensations of bladder filling [ 22 ]. Another study with ambulatory urodynamics in patients with SCL described that 73% reported bladder sensation daily, and 41% experienced DOA [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurogenic detrusor overactivity (NDO) is the most common presentation of neurogenic bladder dysfunction following SCI. 1 NDO results in spontaneous reflex bladder contractions at lower bladder volumes, causing urinary incontinence, feelings of urgency, and low bladder capacity. Approximately two thirds of individuals with SCI have upper motor neuron injuries 2 that are associated with bladder reflexes and the distribution depends on spinal level.…”
Section: Introductionmentioning
confidence: 99%